Anxiety Death and its Relation to Emotional Security – Field Study with the specimens of students of Faculty of Education – University of Aden – - Haydara, Sana Muhammad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to reveal the natural relation between the anxiety death and Emotional security among the specimen students of educated faculty university of Aden, to Identify the level of all the anxiety of death and Emotional security of the specimen members of study. And to find out if there are statistical differences at the level 0,05 among the average grades of the students the researched specimens according to the criteria of the anxiety death and Emotional security according to the changing educational standard (in the first and the third). The specimens research was made up of (446) male and female students of the students of the faculty of education in the university of Aden. then they have been chosen random, and the anxiety death criteria applied on to them prepared by AL-omer (2016) and criteria psychological security prepared by NAEISA (2014) after their verification of their credibility and authenticity. The researcher used the descriptive method Correlative to the appropriateness of the nature of the study problem and its objectives and the results inquired of the study on the existence of a weak positive correlation between anxiety death and psychological security, where the link (rate * 0.153) was also the arithmetic average reached total degree of scale anxiety death (2.09) and (2.13) for Emotional security. And the existence of essential differences between the sample members in the anxiety of death in favor of the third level. And no differences between specimen members average in the Emotional security among the first and third. And the top important recommendations that the research have been reached about the necessity to create guideline program to mitigate the level of anxiety of death or to set rehabilitation course to extent the awareness with the importance of to fulfill the Psychological tranquility to University students furthermore to establish consultant office to guidance and direction in Aden University to discuss the future problems with the academic students.
Keywords: Death Anxiety; Emotional security; Students of the Faculty of Education; University of Aden